Hereditary Systemic Autoinflammatory Diseases: Therapeutic Stratification - Kul Cinar, Ovgu; Putland, Amber; Wynne, Karen; Eleftheriou, Despina; Brogan, Paul A. (Frontiers in Pediatrics, 2022)
Hereditary systemic autoinflammatory diseases (SAIDs) are rare, often severe conditions characterized by mutations in the key regulators of innate immune responses. Dramatic advances in the molecular genetics and next-generation sequencing in the past decade enabled identification of novel mutations that play a pivotal role in the mechanistic pathways of inflammation. Although genetic testing may not always provide straightforward guidance in diagnosis and clinical decision making, through translational research, it sheds light into molecular immunopathogenesis, particularly in IL-1 inflammasome and cytokine signalling pathways. These remarkable insights provided a better understanding of autoinflammatory conditions and their association with the innate and adaptive immune systems, as well as leading to development of cytokine-targeted biologic treatments. Use of targeted therapeutics not only helps control disease flares, reduce acute-phase responses and prevent devastating complications such as amyloidosis, but also improves health-related quality of lives and support patients to pursue almost a normal life. Herein, we discuss the commonest monogenic SAIDs, describe their immunopathology, and summarise the approaches in the management and targeted treatment of these conditions, including presentation of novel data based on a cohort of children with these rare diseases from a single quaternary referral centre in London.